Seawater-corrosion-resistant long-life stainless steel wire rope and preparation method thereof
By adding rare earth cerium to austenitic stainless steel and combining heat treatment, galvanizing, annealing and chromium-free zinc aluminum coating, the problem of insufficient corrosion resistance of stainless steel wire ropes in marine environments is solved, achieving a longer service life and better corrosion resistance of seawater.
Patent Information
- Application Number
- CN202411888766.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-22
AI Technical Summary
Existing stainless steel wire ropes are difficult to maintain high corrosion resistance in marine environments for a long time, resulting in a short service life in seawater.
By adding rare earth cerium to austenitic stainless steel, a stable passivation film is formed, combined with multi-step processes of heat treatment, galvanizing, annealing and chromium-free zinc-aluminum coating, the corrosion resistance of stainless steel wire ropes is improved.
It significantly improves the corrosion resistance and service life of stainless steel wire ropes in seawater, and can maintain stable performance in seawater for more than 58 days.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel wire ropes, in particular to a seawater corrosion-resistant long-life stainless steel wire rope and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology and the national economy, the development and utilization of the earth's polar and marine resources are the research and development focus of countries around the world; among them, human beings have been using the ocean for thousands of years, and in the early days they were mainly concentrated in coastal and offshore fisheries, salt industry and transportation. In the later period, with the development of science and technology and the increase in resource demand, marine development has entered a new stage, including the large-scale development of submarine oil, natural gas, and mineral deposits, the establishment of tidal power stations and desalination plants, as well as emerging industries such as marine aquaculture, deep-sea mining, and wave power generation. In modern marine development, the output value of oil and natural gas development accounts for about 70% of the total output value of marine development. Industries such as marine aquaculture, seawater desalination, and tidal power generation are also developing rapidly. With the increasing development and utilization of the ocean in my country, various marine equipment and energy supply problems have followed one after another. For example, most marine equipment will be exposed to the marine environment for a long time, and there are great requirements for the performance of the materials used. Not only do they need to have excellent mechanical properties, but they also need to have good corrosion resistance. In marine engineering, stainless steel wire ropes are mainly used to build large offshore platforms, offshore drilling platforms, subsea drilling equipment, oil and gas pipelines, and submarine cables. These applications require the wire ropes to have high strength, wear resistance, and corrosion resistance; in order to ensure the long-term stability and safety of stainless steel wire ropes in the marine environment, the production process still needs to be continuously optimized. Summary of the invention
[0003] The object of the present invention is to provide a stainless steel wire rope resistant to seawater corrosion and having a long service life and a preparation method thereof, so as to solve the problems raised in the prior art.
[0004] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope specifically comprises the following steps: Step 1: Select austenitic stainless steel wire rods, perform heat treatment, pickling, phosphating in sequence, and then continuously draw for 7 times to obtain pre-drawn stainless steel wire with a specification of 8-10 mm; Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it, wipe it, cool it, and then anneal it. After annealing, draw it again for 8-10 times to obtain a finished stainless steel wire with a specification of 1-3 mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, dip it in chromium-free zinc-aluminum coating liquid, spin dry, bake and solidify it to obtain a coating with a thickness of 30μm, dip it in sealing coating after cooling, dry it and then apply lubricating grease, and use parallel twisting to obtain a stainless steel wire rope.
[0005] Among them, the specific chemical composition of the austenitic stainless steel wire rod in step 1 includes, by mass percentage, 16-18% Ni, 14.5-14.7% Cr, 5.5-6.0% Si, 1.02-1.05% Mo, 1.08-1.30% Mn, C≤0.020%, P≤0.020%, S≤0.004%, 0.01-0.05% Ce and the balance is Fe.
[0006] In step 1, the heat treatment is carried out by heating the temperature to 1150-1200°C at 10°C / s, keeping the temperature for 8-12 hours and then cooling the temperature to room temperature with water; The zinc layer mass obtained by hot-dip galvanizing in step 2 is 200-240g / m 2 ; During the annealing treatment, the annealing temperature is 1000-1100°C and the annealing time is 2-3h.
[0007] In step 3, the chromium-free zinc-aluminum coating solution includes the following raw materials in percentage by mass: 15-20% modified flaky zinc-aluminum alloy powder, 0.1-0.3% modified graphene, 8-10% ethylene glycol, 6-8% Tween-20, 1-2% hydroxyethyl cellulose, 1.5-2.0% corrosion inhibitor, 10-15% binder, 1-2% defoamer, 30-40% silane hydrolyzate, and deionized water is added to 100%; the baking and curing treatment includes pre-baking at 80-100°C for 8-10 minutes, and then transferring to 270-320°C for baking for 12-15 minutes for curing.
[0008] The preparation steps of the modified flaky zinc-aluminum alloy powder are as follows: pretreating the flaky zinc-aluminum alloy powder, placing it in anhydrous ethanol, ultrasonically cleaning it for 10 minutes, and then rinsing and drying it; mixing the silane coupling agent KH570, anhydrous ethanol and deionized water, adjusting the pH to 4, stirring at a constant temperature of 35°C for 1 hour, standing for hydrolysis overnight to obtain a KH570 hydrolyzate, mixing the pretreated flaky zinc-aluminum alloy powder with the above-mentioned KH570 hydrolyzate, stirring at 40°C for 3 hours, adding an acrylic acid solution diluted with anhydrous ethanol and azobisisobutyronitrile, heating to 70°C, continuing to stir for 6 hours, filtering and washing, and obtaining the modified flaky zinc-aluminum alloy powder.
[0009] The preparation steps of modified graphene are as follows: adding nickel nitrate hexahydrate and rare earth nitrate to deionized water, and ultrasonicating for 20 minutes for standby; placing graphene oxide in deionized water, adding sodium citrate and stirring for 10 minutes after ultrasonic dispersion, placing it in the above nitrate solution and ultrasonicating for 20 minutes, and then transferring it to a reactor, reacting at 160-180° C. for 12 hours, cooling to room temperature, washing and freeze-drying to obtain the modified graphene; Preferably, the rare earth nitrate is any one of cerium nitrate, lanthanum nitrate and yttrium nitrate.
[0010] The preparation steps of chromium-free zinc-aluminum coating are as follows: Step s1: Place zirconium nitrate in deionized water, stir to dissolve, add ethanol and silane coupling agent in sequence, adjust the pH to 4-5, stir at a constant temperature of 35° C. for 1 hour, and stand for hydrolysis overnight to obtain a silane hydrolyzate; Step s2: Mix and stir the modified flaky zinc-aluminum alloy powder and ethylene glycol, add deionized water and Tween-20 in sequence and stir evenly, then add modified graphene, hydroxyethyl cellulose, corrosion inhibitor and binder, and stir at a speed of 150 r / min for 30 minutes to obtain a metal slurry; Step s3: Mix the silane hydrolyzate obtained in steps s1 and s2 with the metal slurry, add a defoamer after stirring at 1500 r / min for 2-3 hours, and continue stirring at 150 r / min for 20-30 minutes to obtain a chromium-free zinc-aluminum coating solution.
[0011] In step s1, the silane coupling agent is one or a combination of two of bis-[γ-(triethoxysilyl)propyl]-tetrasulfide silane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane.
[0012] The stainless steel wire rope obtained by the above preparation method has an 8×61 structure, including a rope core and rope outer strands; the rope outer strands adopt a 61FWS structure; the rope core is composed of core outer strands and core center strands, both of which adopt a 36WS structure.
[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention combines the corrosion phenomenon of stainless steel in the marine environment, such as the chloride ions in seawater that easily cause pitting at the inclusion defects in the steel, and proposes to add rare earth cerium to the prepared austenitic stainless steel to convert the above inclusions into rare earth inclusions, refine the grains, reduce cracks, form a stable passivation film, and improve the corrosion resistance of the main austenitic stainless steel. Then, heat treatment is performed to improve the thermoplasticity of the austenitic stainless steel wire rod, reduce the loss of the torsional performance of the steel wire by hot-dip galvanizing in the later stage, and improve the quality pass rate of the galvanized layer; after the heat treatment, pre-drawing, galvanizing, and annealing are performed to improve the bonding force between the galvanized layer and the base stainless steel material, eliminate internal stress, and then draw and wire draw, dip-coat the prepared stainless steel wire with aluminum zinc coating, bake and solidify to form a corrosion-resistant coating, and then apply a sealing coating for passivation to further improve the corrosion resistance of the coating; then apply lubricating grease, twist into a rope, and reduce material loss during operation.
[0014] 2. The chromium-free zinc-aluminum coating prepared by the present invention uses flaky zinc-aluminum alloy powder as the main anti-corrosion material, and performs coating modification to form an acrylic acid / KH570 protective layer on the zinc-aluminum alloy powder, which improves the dispersibility of the flaky zinc-aluminum alloy powder in the coating on the one hand, and improves the corrosion resistance of the coating after curing on the other hand; modified graphene is added to the coating, and nickel oxide and rare earth oxide are added to the prepared modified graphene, which can participate in the mesh bonding structure of the silane film, be evenly dispersed, improve the density of the coating, effectively slow down the penetration of the corrosive medium, and further improve the corrosion resistance of the coating in seawater; the silane hydrolyzate uses a two-component silane material to improve the corrosion resistance of the coating. DETAILED DESCRIPTION
[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] In the experiment, the specific chemical composition of the austenitic stainless steel wire rod includes 17.05% Ni, 14.67% Cr, 5.88% Si, 1.03% Mo, 1.28% Mn, 0.018% C, 0.020% P, 0.004% S, 0.03% Ce and the balance is Fe in terms of mass percentage; The pickling was carried out with 15% hydrochloric acid for 60 seconds. The phosphating solution used for phosphating was made up to 100% by 25% phosphoric acid, 5% zinc oxide, 24% zinc nitrate, 3% calcium nitrate, 3% sodium nitrite and deionized water, and the treatment lasted for 60 seconds. The sealing coating was purchased from Nanjing Kerun Industry, model KR-SS910; For lubricating grease, use Metrun WRG3600; The preparation steps of chromium-free zinc-aluminum coating are as follows: Step s1: placing zirconium nitrate in deionized water, stirring to dissolve, adding ethanol and silane coupling agent in turn, mixing, adjusting the pH to 4, stirring at a constant temperature of 35° C. for 1 hour, standing for hydrolysis overnight, and obtaining a silane hydrolyzate; wherein the volume ratio of the silane coupling agent, ethanol, and deionized water is 1:1:8; the zirconium nitrate accounts for 0.5% of the silane hydrolyzate; the silane coupling agent is a combination of silane coupling agent Si-69 and octadecyltrimethoxysilane, and the volume ratio is 2:1; Step s2: Mix and stir the modified flaky zinc-aluminum alloy powder and ethylene glycol, add deionized water and Tween-20 in sequence and stir evenly, then add modified graphene, hydroxyethyl cellulose, corrosion inhibitor and binder, and stir continuously at a speed of 150 r / min for 30 minutes to obtain a metal slurry; wherein the corrosion inhibitor is sodium molybdate and the binder is acrylic resin; Step s3: Mix the silane hydrolyzate obtained in steps s1 and s2 with the metal slurry, stir at 1500 r / min for 2 hours, add a defoamer, and continue stirring at 150 r / min for 30 minutes until there are no bubbles, to obtain a chromium-free zinc-aluminum coating solution; wherein the defoamer is sodium chloride.
[0017] The preparation steps of the modified flaky zinc-aluminum alloy powder are as follows: The flaky zinc-aluminum alloy powder was pretreated, placed in anhydrous ethanol, ultrasonically cleaned for 10 minutes, and then rinsed and dried; 6g of silane coupling agent KH570, 80mL of anhydrous ethanol and 20mL of deionized water were mixed and stirred, the pH was adjusted to 4, and the mixture was stirred at a constant temperature of 35°C for 1h, and hydrolyzed overnight to obtain a KH570 hydrolyzate; 5g of the pretreated flaky zinc-aluminum alloy powder was mixed with the above-mentioned KH570 hydrolyzate, and after stirring at 40°C for 3h, 1.5g of acrylic acid and 0.05g of azobisisobutyronitrile diluted with 10mL of anhydrous ethanol were added, the temperature was raised to 70°C, stirring was continued for 6h, and the mixture was filtered and washed to obtain the modified flaky zinc-aluminum alloy powder.
[0018] The flaky zinc-aluminum alloy powder ZnAl20 used above was purchased from Hunan 369 Metallurgy, with a flake diameter of 15-20 μm; The preparation steps of modified graphene are as follows: add 0.6g nickel nitrate hexahydrate and 0.5g rare earth nitrate to 100mL deionized water, and ultrasonicate for 20min for standby use; place 0.5g graphene oxide in 20mL deionized water, add 0.16g sodium citrate after ultrasonic dispersion and stir for 10min, place in the above nitrate solution and ultrasonicate for 20min, then transfer to a reactor, react at 180°C for 12h, cool to room temperature, wash and freeze-dry to obtain the modified graphene; wherein the rare earth nitrate is lanthanum nitrate, and the particle size of graphene oxide is 2-3nm.
[0019] Embodiment 1: This embodiment provides a method for preparing a stainless steel wire rope that is resistant to seawater corrosion and has a long service life. The specific steps are as follows: Step 1: Select an austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is raised to 1200°C at 10°C / s, kept at this temperature for 8 hours, and then cooled to room temperature with water. The wire is pickled and phosphated in turn, and then drawn continuously for 7 times to obtain a pre-drawn stainless steel wire with a specification of 10 mm. Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it to obtain a zinc layer with a mass of 225g / m 2 , wipe and cool, then anneal for 3 hours, set the annealing temperature to 1000℃, and after annealing, perform 10 continuous drawing again to obtain a finished stainless steel wire with a specification of 2.25mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, then dip-coat it with chromium-free zinc-aluminum coating liquid, spin dry and bake to solidify, obtain a coating with a thickness of 30 μm, cool it and dip-coat it with a sealing coating, dry it and obtain a sealing coating with a thickness of 20 μm; then apply lubricating grease, the coating amount is 100 mL / m 2 , parallel twisting is used to obtain a stainless steel wire rope with a structure of 8×61.
[0020] Among them, the chromium-free zinc-aluminum coating includes the following raw materials in percentage by mass: 20% modified flaky zinc-aluminum alloy powder, 0.3% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolyzate, and deionized water is added to 100%; the baking and curing treatment includes pre-baking at 80°C for 10 minutes, and then transferring to 300°C for baking for 12 minutes for curing.
[0021] Embodiment 2: This embodiment provides a method for preparing a stainless steel wire rope that is resistant to seawater corrosion and has a long service life. The specific steps are as follows: Step 1: Select an austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is raised to 1200°C at 10°C / s, kept at this temperature for 8 hours, and then cooled to room temperature with water. The wire is pickled and phosphated in turn, and then drawn continuously for 7 times to obtain a pre-drawn stainless steel wire with a specification of 10 mm. Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it to obtain a zinc layer with a mass of 225g / m 2 , wipe and cool, then anneal for 3 hours, set the annealing temperature to 1000℃, and after annealing, perform 10 continuous drawing again to obtain a finished stainless steel wire with a specification of 2.25mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, then dip-coat it with chromium-free zinc-aluminum coating liquid, spin dry and bake to solidify, obtain a coating with a thickness of 30 μm, cool it and dip-coat it with a sealing coating, dry it and obtain a sealing coating with a thickness of 20 μm; then apply lubricating grease, the coating amount is 100 mL / m 2 , parallel twisting is used to obtain a stainless steel wire rope with a structure of 8×61.
[0022] Among them, the chromium-free zinc-aluminum coating includes the following raw materials in percentage by mass: 15% modified flaky zinc-aluminum alloy powder, 0.1% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 35% silane hydrolyzate, and deionized water is added to 100%; the baking and curing treatment includes pre-baking at 80°C for 10 minutes, and then transferring to 270°C for baking for 15 minutes for curing.
[0023] Embodiment 3: This embodiment provides a method for preparing a stainless steel wire rope that is resistant to seawater corrosion and has a long service life. The specific steps are as follows: Step 1: Select an austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is raised to 1200°C at 10°C / s, kept at this temperature for 8 hours, and then cooled to room temperature with water. The wire is pickled and phosphated in turn, and then drawn continuously for 7 times to obtain a pre-drawn stainless steel wire with a specification of 10 mm. Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it to obtain a zinc layer with a mass of 225g / m 2 , wipe and cool, then anneal for 3 hours, set the annealing temperature to 1000℃, and after annealing, perform 10 continuous drawing again to obtain a finished stainless steel wire with a specification of 2.25mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, then dip-coat it with chromium-free zinc-aluminum coating liquid, spin dry and bake to solidify, obtain a coating with a thickness of 30 μm, cool it and dip-coat it with a sealing coating, dry it and obtain a sealing coating with a thickness of 20 μm; then apply lubricating grease, the coating amount is 100 mL / m 2 , parallel twisting is used to obtain a stainless steel wire rope with a structure of 8×61.
[0024] Among them, the chromium-free zinc-aluminum coating includes the following raw materials in percentage by mass: 20% modified flaky zinc-aluminum alloy powder, 0.2% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 35% silane hydrolyzate, and deionized water is added to 100%; the baking and curing treatment includes pre-baking at 80°C for 10 minutes, and then transferring to 300°C for baking for 12 minutes for curing.
[0025] Embodiment 4: This embodiment provides a method for preparing a stainless steel wire rope that is resistant to seawater corrosion and has a long service life. The specific steps are as follows: Step 1: Select an austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is raised to 1200°C at 10°C / s, kept at this temperature for 8 hours, and then cooled to room temperature with water. The wire is pickled and phosphated in turn, and then drawn continuously for 7 times to obtain a pre-drawn stainless steel wire with a specification of 10 mm. Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it to obtain a zinc layer with a mass of 225g / m 2 , wipe and cool, then anneal for 3 hours, set the annealing temperature to 1000℃, and after annealing, perform 10 continuous drawing again to obtain a finished stainless steel wire with a specification of 2.25mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, then dip-coat it with chromium-free zinc-aluminum coating liquid, spin dry and bake to solidify, obtain a coating with a thickness of 30 μm, cool it and dip-coat it with a sealing coating, dry it and obtain a sealing coating with a thickness of 20 μm; then apply lubricating grease, the coating amount is 100 mL / m 2 , parallel twisting is used to obtain a stainless steel wire rope with a structure of 8×61.
[0026] Among them, the chromium-free zinc-aluminum coating includes the following raw materials in percentage by mass: 20% modified flaky zinc-aluminum alloy powder, 0.3% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolyzate, and deionized water to 100%; the baking and curing treatment includes pre-baking at 80°C for 10 minutes, and then transferring to 320°C for baking for 15 minutes for curing.
[0027] Comparative Example 1: In the control experiment of Example 1, the flaky zinc-aluminum alloy powder is not subjected to modification treatment, and the specific steps are as follows: Step 1: Select an austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is raised to 1200°C at 10°C / s, kept at this temperature for 8 hours, and then cooled to room temperature with water. The wire is pickled and phosphated in turn, and then drawn continuously for 7 times to obtain a pre-drawn stainless steel wire with a specification of 10 mm. Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it to obtain a zinc layer with a mass of 225g / m 2 , wipe and cool, then anneal for 3 hours, set the annealing temperature to 1000℃, and after annealing, perform 10 continuous drawing again to obtain a finished stainless steel wire with a specification of 2.25mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, then dip-coat it with chromium-free zinc-aluminum coating liquid, spin dry and bake to solidify, obtain a coating with a thickness of 30 μm, cool it and dip-coat it with a sealing coating, dry it and obtain a sealing coating with a thickness of 20 μm; then apply lubricating grease, the coating amount is 100 mL / m 2 , parallel twisting is used to obtain a stainless steel wire rope with a structure of 8×61.
[0028] Among them, the chromium-free zinc-aluminum coating includes the following raw materials in percentage by mass: 20% flaky zinc-aluminum alloy powder, 0.3% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolyzate, and deionized water is added to 100%; the baking and curing treatment includes pre-baking at 80°C for 10 minutes, and then transferring to 300°C for baking for 12 minutes for curing.
[0029] Comparative Example 2: A control experiment of Example 1 without adding modified graphene, the specific steps are as follows: Step 1: Select an austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is raised to 1200°C at 10°C / s, kept at this temperature for 8 hours, and then cooled to room temperature with water. The wire is pickled and phosphated in turn, and then drawn continuously for 7 times to obtain a pre-drawn stainless steel wire with a specification of 10 mm. Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it to obtain a zinc layer with a mass of 225g / m 2 , wipe and cool, then anneal for 3 hours, set the annealing temperature to 1000℃, and after annealing, perform 10 continuous drawing again to obtain a finished stainless steel wire with a specification of 2.25mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, then dip-coat it with chromium-free zinc-aluminum coating liquid, spin dry and bake to solidify, obtain a coating with a thickness of 30 μm, cool it and dip-coat it with a sealing coating, dry it and obtain a sealing coating with a thickness of 20 μm; then apply lubricating grease, the coating amount is 100 mL / m 2 , parallel twisting is used to obtain a stainless steel wire rope with a structure of 8×61.
[0030] Among them, the chromium-free zinc-aluminum coating includes the following raw materials in percentage by mass: 20% modified flaky zinc-aluminum alloy powder, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolyzate, and deionized water to 100%; the baking and curing treatment includes pre-baking at 80°C for 10 minutes, and then transferring to 300°C for baking for 12 minutes for curing.
[0031] Detection test 1. Corrosion test: prepare an artificial seawater solution, according to NaCl 24.53 g / L, Na2SO4 4.09 g / L, NaHCO3 0.201 g / L, KCl 0.695 g / L, MgCl2·6H2O 11.1 g / L, CaCl2 1.16 g / L, KBr 0.101 g / L and 1 L H2O, add NaOH to adjust the solution pH to 8.2; cut 1m of the sample prepared in Example 1-4 and Comparative Example 1-2 and immerse it in the above 25°C artificial seawater solution, replace the solution every 3h until pitting occurs on the test surface, and record the time; 2. Breaking tensile test: According to GB / T 38814, the steel wire ropes prepared in Examples 1-4 and Comparative Examples 1-2 were taken, 3 m was cut as the most effective test section length, the specimens were clamped, and tested on a static fatigue machine. A load of 200 N was applied, and the fatigue number was set to 5000 times. After 5000 times, tension was applied to the prepared specimens until they broke. The data were recorded in the following table.
[0032]
[0033] Summary: It can be seen from the above experimental data that the coating formulation used in Example 1 achieves better experimental results than the other examples, with excellent seawater corrosion resistance and a service life of up to 58 days; Comparative Example 1 is a control experiment of Example 1, and the zinc-aluminum alloy powder is not coated and modified with reference to Example 1, and the corrosion resistance is significantly reduced, which is similar to the result of Comparative Example 2 without adding modified graphene; and when the breaking tensile test is performed, the data does not drop significantly, because the peeling of the coating causes the later test of the wire rope to be reflected in the main material of the wire rope, so the drop is not obvious; in summary, the stainless steel wire rope made by the present invention has excellent seawater corrosion resistance and fatigue resistance.
[0034] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope, characterized in that: The specific steps include: Step 1: Select austenitic stainless steel wire rods, perform heat treatment, pickling, phosphating in sequence, and then continuously draw for 7 times to obtain pre-drawn stainless steel wire with a specification of 8-10 mm; Step 2: Degrease and wash the pre-drawn stainless steel wire obtained in step 1, then hot-dip galvanize it, wipe it, cool it, and then anneal it. After annealing, draw it again for 8-10 times to obtain a finished stainless steel wire with a specification of 1-3 mm; Step 3: Degrease and wash the finished stainless steel wire obtained in step 2, dip it in chromium-free zinc-aluminum coating liquid, spin dry, bake and solidify it to obtain a coating with a thickness of 30μm, dip it in sealing coating after cooling, dry it and then apply lubricating grease, and use parallel twisting to obtain a stainless steel wire rope.
2. The method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope according to claim 1, characterized in that: The specific chemical composition of the austenitic stainless steel wire rod in the step 1 includes, by mass percentage, 16-18% Ni, 14.5-14.7% Cr, 5.5-6.0% Si, 1.02-1.05% Mo, 1.08-1.30% Mn, C≤0.020%, P≤0.020%, S≤0.004%, 0.01-0.05% Ce and the balance is Fe.
3. The method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope according to claim 1, characterized in that: In step 1, the heat treatment is carried out at a rate of 10°C / s to a temperature of 1150-1200°C, and then the temperature is kept for 8-12 hours and then cooled to room temperature with water; in step 2, the zinc surface quality obtained by hot-dip galvanizing is 200-240g / m 2 ; During the annealing treatment, the annealing temperature is 1000-1100°C and the annealing time is 2-3h.
4. The method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope according to claim 1, characterized in that: The chromium-free zinc-aluminum coating solution in step 3 includes the following raw materials in percentage by mass: 15-20% modified flaky zinc-aluminum alloy powder, 0.1-0.3% modified graphene, 8-10% ethylene glycol, 6-8% Tween-20, 1-2% hydroxyethyl cellulose, 1.5-2.0% corrosion inhibitor, 10-15% binder, 1-2% defoamer, 30-40% silane hydrolyzate, and deionized water is added to 100%; the baking and curing treatment includes pre-baking at 80-100°C for 8-10 minutes, and then transferring to 270-320°C for baking for 12-15 minutes for curing.
5. The method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope according to claim 4, characterized in that: The preparation steps of the modified flaky zinc-aluminum alloy powder are as follows: pretreating the flaky zinc-aluminum alloy powder, placing it in anhydrous ethanol, ultrasonically cleaning it for 10 minutes, and then rinsing and drying it; mixing and stirring a silane coupling agent KH570, anhydrous ethanol and deionized water, adjusting the pH to 4, stirring at a constant temperature of 35°C for 1 hour, standing and hydrolyzing overnight to obtain a KH570 hydrolyzate, mixing the pretreated flaky zinc-aluminum alloy powder with the above-mentioned KH570 hydrolyzate, stirring at 40°C for 3 hours, adding an acrylic acid solution diluted with anhydrous ethanol and azobisisobutyronitrile, heating to 70°C, continuing to stir for 6 hours, filtering and washing, and obtaining the modified flaky zinc-aluminum alloy powder.
6. The method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope according to claim 4, characterized in that: The preparation steps of the modified graphene are as follows: adding nickel nitrate hexahydrate and rare earth nitrate to deionized water, and ultrasonicating for 20 minutes for standby; placing graphene oxide in deionized water, adding sodium citrate and stirring for 10 minutes after ultrasonic dispersion, placing it in the above nitrate solution and ultrasonicating for 20 minutes, and then transferring it to a reactor, reacting at 160-180° C. for 12 hours, cooling to room temperature, washing and freeze-drying to obtain the modified graphene; wherein the rare earth nitrate is any one of cerium nitrate, lanthanum nitrate and yttrium nitrate.
7. The method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope according to claim 1, characterized in that: The preparation steps of the chromium-free zinc-aluminum coating solution are as follows: Step s1: Place zirconium nitrate in deionized water, stir to dissolve, add ethanol and silane coupling agent in sequence, adjust the pH to 4-5, stir at a constant temperature of 35° C. for 1 hour, and stand for hydrolysis overnight to obtain a silane hydrolyzate; Step s2: Mix and stir the modified flaky zinc-aluminum alloy powder and ethylene glycol, add deionized water and Tween-20 in sequence and stir evenly, then add modified graphene, hydroxyethyl cellulose, corrosion inhibitor and binder, and stir at a speed of 150 r / min for 30 minutes to obtain a metal slurry; Step s3: Mix the silane hydrolyzate obtained in steps s1 and s2 with the metal slurry, add a defoamer after stirring at 1500 r / min for 2-3 hours, and continue stirring at 150 r / min for 20-30 minutes to obtain a chromium-free zinc-aluminum coating solution.
8. The method for preparing a seawater corrosion-resistant and long-life stainless steel wire rope according to claim 7, characterized in that: In step s1, the silane coupling agent is one or a combination of two of bis-[γ-(triethoxysilyl)propyl]-tetrasulfide silane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane.
9. The stainless steel wire rope obtained by the preparation method according to any one of claims 1 to 4, characterized in that: The stainless steel wire rope is of 8×61 structure, with a nominal diameter of 96 mm, and comprises a rope core and outer strands; the outer strands of the rope adopt a 61FWS structure; the rope core is composed of outer strands and core center strands, both of which adopt a 36WS structure.
Citation Information
Patent Citations
Chromium-manganese-copper-molybdenum series austenite corrosion-resistant wear-proof stainless steel
CN101148740A
Low-carbon steel stranded wire and production process thereof
CN102747624A
Stainless steel wire rope and production process thereof
CN103498112A
High-strength austenitic stainless steel for automobile frames and manufacturing method thereof
CN104120368A
Method for manufacturing highly corrosion-resistant steel wire rope for fishery
CN104928956A